School and Power: A Rebellious Approach - Meoño Soto, Rodolfo (2003)
With the appearance in highly industrialized countries of a youth movement of a rebellious nature towards the so-called globalization process of the market economy, interest in North American Critical Pedagogy has resumed in intellectual circles. The purpose of this essay is, then, the examination of the fundamental critical theories of these pedagogical currents in North America, developed by Henry Giroux, an American and Peter McClaren of Canadian origin.